CO2 capture from natural gas combined cycles by CO2 selective membranes. (June 2017) - Turi, D.M.; Ho, M.; Ferrari, M.C.; Chiesa, P.; Wiley, D.E.; Romano, M.C.
Highlights: Process integration study and economic analysis of CO2 membranes in combined cycles are performed. Wide sensitivity analysis on membrane pressures and GT pressure ratio is performed. Combining high selectivity membrane for CO2 capture and high permeability membrane for CO2 recycle gives the best performance. At membrane costs below 50 US$/m 2, the process is competitive with a benchmark plant featuring CO2 capture by MEA solvent. The need of a substantial redesign of gas turbine components represents a major hurdle for the commercial deployment. Abstract: This paper performs a techno-economic analysis of natural gas-fired combined cycle (NGCC) power plants integrated with CO2 selective membranes for post-combustion CO2 capture. The configuration assessed is based on a two-membrane system: a CO2 capture membrane that separates the CO2 for final sequestration and a CO2 recycle membrane that selectively recycles CO2 to the gas turbine compressor inlet in order to increase the CO2 concentration in the gas turbine flue gas. Three different membrane technologies with different permeability and selectivity have been investigated. The mass and energy balances are calculated by integrating a power plant model, a membrane model and a CO2 purification unit model. An economic model is then used to estimate the cost of electricity and of CO2 avoided. A sensitivity analysis on the main process parameters and economic assumptions is also performed. It was found that a combination of a high permeability membrane with moderate selectivity as a recycle membrane and a very high selectivity membrane with high permeability used for the capture membrane resulted in the lowest CO2 avoided cost of 75 US$/tCO2 . This plant features a feed pressure of 1.5 bar and a permeate pressure of 0.2 bar for the capture membrane. This result suggests that membrane systems can be competitive for CO2 capture from NGCC power plants when compared with MEA absorption. However, to achieve significant advantages with respect to benchmark MEA capture, better membrane permeability and lower costs are needed with respect to the state of the art technology. In addition, due to the selective recycle, the gas turbine operates with a working fluid highly enriched with CO2 . This requires redesigning gas turbine components, which may represent a major challenge for commercial deployment.